2021
DOI: 10.3389/fimmu.2021.765349
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19: From Dysregulated Immunity to Vaccination Status Quo

Abstract: The development of vaccines against infectious diseases has helped us battle the greatest threat to public health. With the emergence of novel viruses, targeted immunotherapeutics ranging from informed vaccine development to personalized medicine may be the very thing that separates us between life and death. Late in 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of coronavirus disease 2019 (COVID-19), made a remarkable entrance to human civilization, being one of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…Additionally, vaccinated individuals have been found to have lower viral loads compared to non-vaccinated individuals in subsequent episodes of infection, which may contribute to milder symptoms [ 49 ]. Furthermore, it has been reported that non-vaccinated individuals may have immune system dysregulation, leading to more severe symptoms of infection [ [50] , [51] , [52] ]. COVID-19 vaccination can help downregulate the immune response [ 51 ], potentially reducing cell damage and resulting in less severe symptoms, including respiratory symptoms and headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vaccinated individuals have been found to have lower viral loads compared to non-vaccinated individuals in subsequent episodes of infection, which may contribute to milder symptoms [ 49 ]. Furthermore, it has been reported that non-vaccinated individuals may have immune system dysregulation, leading to more severe symptoms of infection [ [50] , [51] , [52] ]. COVID-19 vaccination can help downregulate the immune response [ 51 ], potentially reducing cell damage and resulting in less severe symptoms, including respiratory symptoms and headaches.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, there are currently no variants of high consequence circulating in the United States, but there are four variants of concern in circulation: B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 (Delta), and P.1 (Gamma). Considering most vaccines are designed against the SARS-CoV-2 spike protein, mutations within this region are likely to result in less effective vaccinations ( Escobedo et al., 2021 ). However, a study focusing on the effectiveness of the AstraZeneca and Pfizer vaccines against the predominant variant (B.1.1.7) and the delta variant surging through India and the United Kingdom (B.1.617.2) showed small differences between both vaccines, suggesting that both vaccines may continue to protect against SARS-CoV-2 strains ( Lopez Bernal et al., 2021 ).…”
Section: Origin Of Sars-cov-2mentioning
confidence: 99%